Peran Stakeholder Dalam Reformasi Pendidikan Berbasis Daring Pada Desa 3T Di Kabupaten Sumbawa Nusa Tenggara Barat - Donny Aldise (Universitas 17 Agustus 1945 Semarang, 2024)
Learning in underdeveloped villages is constrained by accessibility problems. Accessibility is not only in terms of area affordability, but also economics, health and the environment. The existence of accessibility which is considered severe has an impact on the quality of education which is categorized as weak. Therefore, remore area education needs many contributions from stakeholders. Then, to overcome this problem should be followed up by providing additional internet facilities to support information and communication facilities, but the use of the internet has not been maximized. The purposes of this analysis are 1) to describe and analyze the problem of weaknesses in using internet technology as a learning tool, and 2) to carry out an analysis of appropriate educational planning for underdeveloped villages. This analysis was carried out using a descriptive qualitative approach. The results of this analysis are 1) the use of the internet to support the learning process is considered not optimal due to the HR factors of teachers and madrasah leader who do not understand online learning, 2) the educational planning process is carried out as a solution to implementation weaknesses, namely by using synoptic theory and increasing competence teacher pedagogy. Conclusion education planning needs to be conducted to increase the output and outcome of the program that has been planned.